2021
DOI: 10.1515/cclm-2021-0199
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of Krebs von den Lungen-6 (KL-6) measurement in idiopathic pulmonary fibrosis: a systematic review and meta-analysis

Abstract: Objectives Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial disease with limited therapeutic options. The measurement of Krebs von den Lungen-6 (KL-6) glycoprotein has been proposed for evaluating the risk of IPF progression and predicting patient prognosis, but the robustness of available evidence is unclear. Methods We searched Medline and Embase databases for peer-reviewed literature from inception to Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…The Krebs von den Lungen-6 (KL-6) protein, as a high-molecular weight mucin glycoprotein, predominantly expressed on the surface of AEC II and bronchial epithelial cells [ 393 ], was proposed as a biomarker of both ALI/ARDS and pulmonary fibrosis due to its localization and the damage sustained by AECs in both diseases. This fact limits the diagnostic utility of KL-6, but several studies have reported its prognostic potential in pulmonary fibrosis [ 369 , 394 ].…”
Section: Prognostic Markers Of Acute Lung Injury and Pulmonary Fibrosismentioning
confidence: 99%
“…The Krebs von den Lungen-6 (KL-6) protein, as a high-molecular weight mucin glycoprotein, predominantly expressed on the surface of AEC II and bronchial epithelial cells [ 393 ], was proposed as a biomarker of both ALI/ARDS and pulmonary fibrosis due to its localization and the damage sustained by AECs in both diseases. This fact limits the diagnostic utility of KL-6, but several studies have reported its prognostic potential in pulmonary fibrosis [ 369 , 394 ].…”
Section: Prognostic Markers Of Acute Lung Injury and Pulmonary Fibrosismentioning
confidence: 99%
“…These observations, however, were not statistically significant. The authors of the meta-analysis highlighted inter-assay disagreement, retrospective design in most studies, and lack of validation in non-Asian subjects as major confounding factors [12].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of SP-A, KL-6 have previously been associated with disease progression and reduced survival in IPAF and IPF patients [31,[55][56][57][58][59][60][61][62][63][64]. Given that a high proportion of patients with IPAF have typical radiological or histological patterns of interstitial pneumonia similar to IPF[61, 65-68], we hypothesized that the biomarkers in IPF that predict clinical outcomes are also associated with IPAF.…”
Section: Discussionmentioning
confidence: 99%